2015
DOI: 10.1002/ccd.26150
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sirolimus eluting stent with bioresorbable polymer to everolimus eluting stent with permanent polymer in bifurcation lesions: Results from CENTURY II trial

Abstract: The new bioresorbable polymer sirolimus-eluting stent showed safety and efficacy profiles similar to durable polymer everolimus-eluting in the treatment of patients with bifurcation lesions at 1-year follow up. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…In our patient group, the incidence of TLF was acceptable (6.4% at 1 year) when considering the higher‐risk baseline patient (e.g., ACS, renal disease) and lesion (e.g., CTO, ISR, calcified lesion) characteristics and comparable to previous studies that have reported similar TLF rates following everolimus‐eluting stent implantation at 1 year . However, in our patient group, bifurcation treatment was associated with high ST rates (1.4%, 2.5%, and 2.5% at 30, 180, and 360 days, respectively) supporting observations in the original GHOST‐EU registry (2.1% at 180 days) as well as other previous published data .…”
Section: Discussionsupporting
confidence: 84%
“…In our patient group, the incidence of TLF was acceptable (6.4% at 1 year) when considering the higher‐risk baseline patient (e.g., ACS, renal disease) and lesion (e.g., CTO, ISR, calcified lesion) characteristics and comparable to previous studies that have reported similar TLF rates following everolimus‐eluting stent implantation at 1 year . However, in our patient group, bifurcation treatment was associated with high ST rates (1.4%, 2.5%, and 2.5% at 30, 180, and 360 days, respectively) supporting observations in the original GHOST‐EU registry (2.1% at 180 days) as well as other previous published data .…”
Section: Discussionsupporting
confidence: 84%
“…The RCT known as the CENTURY II trial, which enrolled 1,119 patients assigned in a 1:1 ratio to receive either BP‐SESs or the Xience stents, demonstrated that the TLR, TLF, and definite ST rates were 2.7%, 4.4%, and 0.9%, respectively, at 9 months after BP‐SES implantation . BP‐SESs also showed similar safety and effectiveness to the permanent polymer everolimus‐eluting Xience stent when used for bifurcation lesions, small vessels, and long lesions . Although the CENTURY II trial included complex lesions, patients of HD and ISR were partially excluded from that study.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the present study adds to the numerous published evidence from recent years on excellent performance of Ultimaster (BP‐SES) system. This includes reports of favorable outcomes in general and specific subpopulations, like STEMI patients, bifurcations, long lesions, and small vessels …”
Section: Discussionmentioning
confidence: 99%